1986
DOI: 10.1159/000112250
|View full text |Cite
|
Sign up to set email alerts
|

Early Expression of Carbonic Anhydrase II (CAII) in Transitory Glial Cells of the Developing Murine Nervous System

Abstract: Using immunocytochemical methods carbonic anhydrase II (CAII) has been detected in the embryonic mouse central nervous system as early as in stage E16. In the spinal cord and the brain stem, the enzyme first appeared in transitory cells probably derived from the radial glia. In the cerebrum such transitory cells were never stained with anti-CAII sera. The bodies of CAII-positive cells were never visualized in the ventricular layer. The controversial cellular specificity of CAII made it impossible to specify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…A certain number of astrocytes may arise from the generative matrix without passing through a previous phase as radial glia (LeVine and Goldman, 1988). Intermediate forms seen in the process of transformation have been described in some rodent species (Benjelloun at al., 1986;Levine and Goldman, 1988). Some of these forms transitorily express carbon anhydrase 11, an oligodendrocyte marker (Benjelloun et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A certain number of astrocytes may arise from the generative matrix without passing through a previous phase as radial glia (LeVine and Goldman, 1988). Intermediate forms seen in the process of transformation have been described in some rodent species (Benjelloun at al., 1986;Levine and Goldman, 1988). Some of these forms transitorily express carbon anhydrase 11, an oligodendrocyte marker (Benjelloun et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these forms transitorily express carbon anhydrase 11, an oligodendrocyte marker (Benjelloun et al, 1986). In this connection, it has been shown that the rat radial glia are a precursor of both astrocytes and oligodendrocytes (Pixley and De Vellis, 1984;Benjelloun et al, 1986;Hirano and Goldman, 1988). The transformation of radial glia into astrocytes may be influenced by neurons that trigger the expression of glial glutamine synthetase, an astrocyte marker (Linser and Perkins, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins have been detected at ED 9 in the mouse brain (Cochard and Paulin, 1984;Foster et al, 1987). The CA I1 protein is widely considered to be a specific oligodendroglial marker; this antigent first appears at ED 16 in the embryonic mouse CNS (Benjelloun et al, 1986). The other markers of oligodendroglial precursor cells (A2B5 and galactocerebroside) appear later (Abney et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Within 18-24 hr of plating, the mRNA+ cells from E-12 hypothalami are very small and have a characteristically high nucleocytoplasmic ratio, as do embryonic cells. The mRNA+ protein+ cells, which appear 4-5 days later, present a bipolar or monopolar aspect, with a very long process at one pole and often a short and thin process at the other pole; they are reminiscent of the CA I1 protein transitory glial cells in the early developing mouse brain (Benjelloun et al, 1986). At the postnatal stage, mRNA+ protein+ cells present the characteristic morphology of the adult oligodendrocyte: a spherical or polygonal cell body with an excentric nucleus (Peters et al, 1976) and occasionally a few delicate processes.…”
Section: Discussionmentioning
confidence: 99%